Determination of Yield and Quality Characteristics of Some Chickpea (Cicer arietinum L.) Varieties Cultivated in Van Ecological Conditions - Mehmet Şerif SARIMURAT; KULAZ, Haluk; ERDİN, Fatih (MAS Journal of Applied Sciences, 2022)
The research was carried out in a randomized block design using 12 registered chickpea cultivarsin 2016 in order to determine the yield and technological properties of some chickpea cultivars in Vanecological conditions. According to the results of the research, plant height, 31.70-39.50 cm, first pod height15.33-20.70 cm, number of branches per plant 4.10-9.76, number of pods per plant 12.26-19.56, number ofseeds per plant 10.43-21.43, biological yield 319.30- 466.06 kg/da, grain yield per unit area 111.73-162.83kg/da, harvest index 34.63-35 %, 100 grain weight 31.66-38.96 g, wet weight 67.10-84.76 g and waterintake capacity 0.26-0.46 g/grain, water absorption index 0.73-1.20%, ash content 3.83-6.00%, proteincontent 18.16-23.00%, wet volume 157.33-174.66 ml and sieve test 5.06-8.10 mm. While the highest grainyield was obtained from Hasanbey variety with 162.83 kg/da, the lowest grain yield was obtained fromAzkan variety with 111.73 kg/da.